Green tea (Camellia sinensis L.) potential to liver of hyperuricemia rats (Rattus norvegicus) fed with high purine diet - NUGRAHENI, PUTRANTY WIDHA; MAHDI, CHANIF; RAHMAWATI, FITRIA; ANALITA, RIZKI NUR (Universitas Syiah Kuala, 2024)
Uric acid is produced in tissues containing xanthine oxidases, like the small intestine and liver, as involved in the purine metabolism of adenine and guanine. High uric acid levels cause damage to cell membranes due to the lipid peroxidase chain reaction. Foods containing high purines will activate the xanthine oxidase (XOD), causing an increase in free radicals. Free radicals attack polyunsaturated fatty acids (PUFA) by forming lipid peroxides. PUFA molecules contain multiple double bonds, which make them susceptible to oxidation by reactive oxygen species (ROS), such as free radicals. PUFA will be broken into simple compounds such as pentane, ethane, and aldehydes, leading to malondialdehyde (MDA) formation. High MDA levels illustrate the process of cell membrane oxidation leading to cell membrane damage. Hyperuricemia is often treated using synthetic drugs such as allopurinol; however, it can cause side effects. Some people will choose medicinal plants with minimal side effects. Green tea (Camellia sinensis L.) contains many polyphenol antioxidants, especially flavonoids, which also have a strong antioxidant effect by exerting multiple mechanisms such as inhibiting several enzymes, including antiphospholipid peroxidase, free radical scavengers, metal bonds, and xanthine oxidase (XOD). Statistical analysis results proved that green tea with a dose of 600 mg/kg BW could decrease the level of MDA in the liver by 84.87% (p 0.01) and reduce the activity of XOD by 35.36% (p 0.01). Taken together, green tea can improve liver histopathology.